Evaluation of Oxidative Stress and Antioxidants in Iraqi Patients with Hydatid Disease - Ahmed A. Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2020)
Antioxidants and oxidative stress status are clinically important in the detection of many diseases. In order to estimate the role of oxidative stress in hydatid disease pathogenesis, the antioxidant levels and oxidative stress status were examined in the patients of hydatid cysts. Thirty patients having active hydatid cyst of Echinococcus granulosus, previously diagnosed by X-ray, were adopted as patients’ group. Additionally, 25 healthy individuals who did not have hydatid infection or any other parasitic infection constituted the control group. Antioxidant status and oxidative stress levels were determined using biochemical tests including plasma Malondialdehyde (MDA) level, and erythrocyte Catalase (CAT), Glutathione Peroxidase (GSH Px), Superoxide Dismutase (SOD), Glutathione-S-Transferase (GST) activity, in addition to erythrocyte Glutathione concentration GSH-conc. The statistical evaluation of plasma MDA levels showed significantly higher levels in hydatid patients than in healthy controls, while erythrocyte SOD, GSH-Px, CAT, GST and GSH levels were significantly declined in hydatid patients compared to the control which can be used as diagnostic markers in the laboratory diagnosis of the disease. To conclude, hydatid patients show elevated oxidative stress status, and therefore, the antioxidant therapy should be considered in addition to the routine medicines in this group of patients.